2004
DOI: 10.1182/blood-2003-03-0930
|View full text |Cite
|
Sign up to set email alerts
|

Direct killing of Epstein-Barr virus (EBV)–infected B cells by CD4 T cells directed against the EBV lytic protein BHRF1

Abstract: We show here that T-cell responses to this particular BHRF1 epitope are shared by most EBV-infected DR*0401 ؉ individuals, as BHRF1-specific CD4 T cells could be sorted out from all the DRB*0401 T-cell lines analyzed, using magnetic beads coated with recombinant BHRF1/DR*0401 complexes. Sorting with these peptide MHC class II multimers was very efficient, as the yield of recovery of BHRF1-specific T cells was nearly 100%. Functional analysis of a large number of clones responding to BHRF1/DR*0401 demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 40 publications
(50 reference statements)
1
63
0
1
Order By: Relevance
“…It is now apparent that a subset of CD4 + T cells expresses both perforin and granzymes (59)(60)(61), and that these cells are capable of killing both in vitro and in vivo. Direct killing in vivo by CD4 + T cells has been shown in several viral infections, including lymphocytic choriomeningitis virus, EBV, and gammaherpesvirus (62)(63)(64), and the presence of CD4 + T cells with a cytotoxic phenotype has been described in HIV-1-infected individuals (65). In fact, studies with CD4 + T cells obtained from HIV-1-infected individuals and healthy controls demonstrated that such CD4 + T cells not only harbor granules containing perforin and granzyme B, but were also able to release them upon specific stimulation with CMV peptides, resulting in lysis of the target cells ex vivo (66).…”
Section: Discussionmentioning
confidence: 99%
“…It is now apparent that a subset of CD4 + T cells expresses both perforin and granzymes (59)(60)(61), and that these cells are capable of killing both in vitro and in vivo. Direct killing in vivo by CD4 + T cells has been shown in several viral infections, including lymphocytic choriomeningitis virus, EBV, and gammaherpesvirus (62)(63)(64), and the presence of CD4 + T cells with a cytotoxic phenotype has been described in HIV-1-infected individuals (65). In fact, studies with CD4 + T cells obtained from HIV-1-infected individuals and healthy controls demonstrated that such CD4 + T cells not only harbor granules containing perforin and granzyme B, but were also able to release them upon specific stimulation with CMV peptides, resulting in lysis of the target cells ex vivo (66).…”
Section: Discussionmentioning
confidence: 99%
“…Protein-secretion inhibitor brefeldin-A (1 mM) was added after 2 hours' incubation. Intracellular staining assays were performed as previously described 18 with anti-IFN-␥ or anti-tumor necrosis factor alpha (TNF-␣) mAb (100 ng/mL, BD Pharmingen, Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…Cytotoxicity was tested by standard 4-h chromium-51 release assay, at defined E:T ratios, as described previously (24). When used, synthetic peptides were directly added to chromium-51-labeled targets and incubated for 1 h before excess unbound peptide was washed off.…”
Section: Lymphocyte Functional Assaysmentioning
confidence: 99%
“…ϩ T cell clones EBV-specific CD4 ϩ T cell clones were derived from PBL from healthy virus carriers or from synovial fluid from patients suffering from rheumatoid arthritis, as described previously (24,25). T cell clones were maintained in RPMI 1640 supplemented with 10% pooled human serum, 1 mM L-glutamine, and 150 IU/ml rIL-2.…”
Section: Ebv-specific Cd4mentioning
confidence: 99%
See 1 more Smart Citation